The Relationship between Tools and Management Support with Nurse Practitioners' Job Satisfaction - Mahardika Putri Kaonang; Tiyas Kusumaningrum; Stefanus Supriyanto (Alta Dharma Publisher, 2020)
Improving the quality of nursing services is done by increasing nurse job satisfaction in order to improve the performance of nurses in improving services. This study aims to identify the relationship between of tools and management support with nurses' job satisfaction in the Dr. Soedomo regional public hospital of Trenggalek Regency. The cross-sectional study design was applied in this study. We recruited 172 nurse practitioner using proportional random sampling. The results showed that there was anrelationship between tools and management support with nurses’ job satisfaction with the tool (p = 0,039 < 0,05), and management support (p = 0,034 <0,05). Improvement of tools and management support can improve nurse job satisfaction